Ta`limu Al Lugho Al Arabiyyah Muassasan Ala Al Iliktiruniyyah E-Learning Tiwalah Ayyami Al Jaihat Litullabi Al Fasli At Tsamin A Bi Al Madrasah Al Tsanuwiyyah Al Hukumiyyah Al Tsaniyah Funuruku: ???????? ???????? ???????? ??????? ???????? A ???? ???? ??????? ????? ????? ?????? (E Learning) ????? ????? ??????? ????? ??? ??????????? - Muh Kemal Fikri Kemal; Moh. Ismail Ismail; Salman Al Farizi Salman (The Center for Language Development, Mataram State Islamic University., 2023)
The implementation of the E-Learning System at MTsN 2 Ponorogo has been around for almost 2 years. I know more precisely, since the corona virus existed, and MTsN 2 Ponorogo is one of the madrasas that use this learning, MTsN 2 Ponorogo itself has an E-Learning system that aims to connect student learning at home due to the corona virus. E Learning itself is an educational system or system that utilizes information technology in the teaching and learning system, Online learning (E Learning) at MTsN 2 ponorogo Using a website (WEB) that uses Asynchronous E Learning where Asynchronous E Learning or Asynchronous learning is a general term used used to describe forms of education, teaching, and learning that occur in the same place and time. It uses resources that facilitate the sharing of information beyond the constraints of time and place. To see the absorption of students in Arabic language material and to find out how the implementation of E Learning, the researchers examined the method of implementing E Learning, and also found out the problems and how to solve them.From the analyzed data, it can be seen that the research results are (1) the application of E Learning learning at MTsN 2 (a) This learning has been set to start from the 2020/2021 school year. (b) Learning in this madrasa includes a Web-Based Learning (WEB) model. (c) Teacher procedures in teaching using the E Learning application. (g) The procedure for students to use the E Learning application in their daily learning is structured. (2) The problems that exist in learning E Learning for class 8A at MTsN 2 Ponorogo. (a) There are problems with the teachers when using this lesson. (b) There are problems with students when using this learning. (3) Solutions to problems that exist in E-Learning for grade 8A children at MTsN 2 Ponorogo. (a) Solutions on how teachers use this learning. (b) Solutions about how students use this learning.Based on this research, the researcher expects (1) Arabic language teachers to increase knowledge in learning, especially in today's era. (2) Arabic teacher to add learning media in E Learning learning. (3) Schools to pay more attention to students in Arabic lessons.